Synthesis of Novel Porphyrin and its Complexes Covalently Linked to Multi-Walled Carbon Nanotubes and Study of their Spectroscopy - Jin Jun; Dong Zhengping; He Jianguo; Li Rong; Ma Jiantai (Nanoscale Research Letters, 2009)
Abstract Novel covalent porphyrin and its complexes (Co2+, Zn2+) functionalized multi-walled carbon nanotubes (MWNTs) have been successfully synthesized by the reaction of the carboxyl on the surface of MWNTs which was synthesized to use carbon radicals generated by the thermal decomposition of azodiisobutyronitrile (AIBN) with 5-p-hydroxyphenyl-10,15,20-triphenyl-porphyrin and its complexes (Co2+, Zn2+). Three resulting nanohybrids were characterized by spectroscopy (FT-IR, Raman, and UV-vis), TGA, and TEM. The quality of porphyrin attached to the MWNTs was determined from thermogravimeric analysis (TGA) of the MWNTs, which showed a weight loss of about 60%. The Raman and absorption spectroscopy data showed that the electronic properties of modified MWNTs were mostly retained, without damaging their one-dimensional electronic properties. From fluorescence measurements, it was observed that the porphyrin and its complexes (Co2+, Zn2+) were nearly quenched by MWNTs, indicating that this covalently modified mode facilitated the effective energy or electron transfer between the excited porphyrin moiety and the extended π-system of MWNTs.